Critical mass for an attraction–repulsion chemotaxis system. Issue 13 (3rd October 2018) - Guo, Qian; Jiang, Zhaoxin; Zheng, Sining
ABSTRACT: This paper determines the critical mass for the attraction–repulsion chemotaxis system:, , , subject to the non-flux boundary condition in a bounded domain with, . It was known that the solutions are globally bounded if . In this paper, we prove with that the solutions must be globally bounded whenever the initial mass, and the finite time blow-up may occur if .